1991
DOI: 10.1212/wnl.41.9.1371
|View full text |Cite
|
Sign up to set email alerts
|

Inherited protein C deficiency and nonhemorrhagic arterial stroke in young adults

Abstract: Out of a consecutive series of 50 young people less than 45 years old with nonhemorrhagic arterial stroke, three patients had inherited protein C deficiency. CT revealed hypodense areas consistent with the clinical picture, and angiography showed occlusion of some intracranial arterial vessels. Other possible associated causes of stroke were ruled out. One patient had a transient ischemic attack and a peripheral venous thrombosis prior to the actual stroke, whereas the others were completely asymptomatic, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 0 publications
1
32
0
2
Order By: Relevance
“…648 Deficiencies of protein C, protein S, or antithrombin III in adults are rare (<1% population) but are associated with increased risk for venous thrombosis. 672 Although case reports 657 and 1 observational cohort study 673 have suggested an association between inherited protein C deficiency and increased risk for ischemic stroke, 674,675 this finding has not been confirmed in case-control studies and meta-analyses. 657 Thus, these rare conditions are of uncertain significance in adults with ischemic stroke.…”
Section: Inherited Thrombophiliasmentioning
confidence: 98%
“…648 Deficiencies of protein C, protein S, or antithrombin III in adults are rare (<1% population) but are associated with increased risk for venous thrombosis. 672 Although case reports 657 and 1 observational cohort study 673 have suggested an association between inherited protein C deficiency and increased risk for ischemic stroke, 674,675 this finding has not been confirmed in case-control studies and meta-analyses. 657 Thus, these rare conditions are of uncertain significance in adults with ischemic stroke.…”
Section: Inherited Thrombophiliasmentioning
confidence: 98%
“…[31][32][33][34] Caseseries studies reported prevalence rates of 0% to 23%. 32,[35][36][37][38][39][40] Hereditary fibrinolytic defects such as plasminogen deficiency have a reported prevalence of 0% to 2.7% in casecontrol and case-series studies of ischemic stroke patients aged Ͻ45 years. 32,35,37,39 These data do not permit calculation of cumulative prevalence rates.…”
Section: Hereditary Coagulation Defectsmentioning
confidence: 99%
“…[2,3,5,15,18,22,23,51,62,79,80,84,100,101] These changes can be found from a few minutes up to 2 weeks after the onset of brain ischemia. It is not clear, however, whether these hemostatic abnormalities precede or follow the neurological event.…”
Section: Hemostatic Theorymentioning
confidence: 98%
“…[112] Resistance to the effects of APC (due to the mutation in factor V gene and homocysteinemia) is closely linked to venous thrombosis in humans [111] and could also be a potential hemostatic risk factor for stroke and heart attack. Recent studies in stroke populations have examined protein C antigen and protein C zymogen activity after in vitro addition of snake venom, or other exogenous activators, [3,18,23,80] as well as the activity of the circulating antithrombotic enzyme, APC. [51] It has been reported that low plasma protein C levels were related to poor outcome after stroke and may have been caused by protein C depletion because of excessive thrombin generation and rapid APC clearance.…”
Section: Antithrombotic Mechanismsmentioning
confidence: 99%